The The Roles of Micro Nutrition Substances (Folic Acid, Vitamin C, Zink) on the Incidence of Anemia in Addolescent Girls - Yunita, Viona Septi; Maigoda, Tonny Cortis (JURNAL PROTEKSI KESEHATAN, 2023)
Anemia is a condition of decreased red blood cell mass characterized by decreased hemoglobin, hematocrit and red blood cell count. Anemia in young women is at risk of impaired physical and mental function and can increase the risk of complications in the future. Based on the World Health Organization (WHO) report which states that more than 30% or 2 billion of the world's population is anemic. The prevalence of anemia in Indonesia is 21.7% with anemia sufferers aged 5-14 years of 26.4% and 57% aged 15-24 years. These data indicate that anemia is a nutritional problem that is often experienced by adolescents. The purpose of this study was to determine the relationship between micronutrients (folic acid, vitamin C, zinc) and the incidence of anemia in students majoring in nutrition at the Poltekkes Kemenkes Bengkulu in 2023. The research design used was cross sectional. The sampling technique used purposive sampling, with a total sample of 53 respondents. data collection using the food recall form. Data analysis using correlation test. The results showed that there was no relationship between micronutrients (folic acid, vitamin C, zinc) and the incidence of anemia (p<0.05). It is recommended to examine other factors that cause anemia that are not examined, such as sleep patterns, knowledge, attitudes, behavior about anemia, especially in young women.